A Bhutan guide for VMY 2020 - Abdul Razak, Dzulkifli (New Straits Times Press (M) Bhd., 2019)
Visit Malaysia Year 2020 logo has been replaced by a new and attractive combination of the hornbill, hibiscus and ferns (paku pakis), Malaysians are relieved. Still, there are challenges that remain daunting, especially in terms of breaking into the 30 million target for inbound visitors. So far the numbers have been relatively low compared with neighbouring countries. To the north, the percentage increase has breached the 100 per cent mark, while to the south it is almost 60 per cent during the same period (from 2010 to 2018). Sadly, Malaysia’s increase is only a single digit at less than five per cent. In terms of numbers, it is on average about two million visitors.